Radiosynthesis and micro-SPECT analysis of triazole-based RGD integrin ligands as non-peptide molecular imaging probes for angiogenesis. Issue 5 (1st March 2015) - Bianchini, Francesca; Fabbrizzi, Pierangelo; Menchi, Gloria; Raspanti, Silvia; Bottoncetti, Anna; Passeri, Alessandro; Andreucci, Elena; Guarna, Antonio; Calorini, Lido; Pupi, Alberto; Trabocchi, Andrea
Graphical abstract: Abstract: Taking advantage of click chemistry, we synthesized triazole-containing RGD peptidomimetics capable of binding to αv β3 integrin with diverse potency, and selected 125 I-labeled compounds proved to interact in vitro and in vivo with αv β3 integrin expressed by melanoma cells. Two 125 I-compounds containing either 2-aminobenzimidazole or 2-aminopyridine groups as the arginine bioisostere with the capacity to selectively bind cells of highly expressing αv β3 melanoma xenografts were found using micro-SPECT imaging studies.